Cooperative Nonbonded Forces Control Membrane Binding of the pH-Low Insertion Peptide pHLIP - Gupta, Chitrak (Biophys J, 2018)
Peptides with the ability to bind and insert into the cell membrane have immense potential in biomedical applications. pH (low) insertion peptide (pHLIP), a water-soluble polypeptide derived from helix C of bacteriorhodopsin, can insert into a membrane at acidic pH to form a stable transmembrane α-helix. The insertion process takes place in three stages: pHLIP is unstructured and soluble in water at neutral pH (state I), unstructured and bound to the surface of a membrane at neutral pH (state II), and inserted into the membrane as an α-helix at low pH (state III). Using molecular dynamics simulations, we have modeled state II of pHLIP and a fast-folding variant of pHLIP, in which each peptide is bound to a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine bilayer surface. Our results provide strong support for recently published spectroscopic studies, namely that pHLIP preferentially binds to the bilayer surface as a function of location of anionic amino acids and that backbone dehydration occurs upon binding. Unexpectedly, we also observed several instances of segments of pHLIP folding into a stable helical turn. Our results provide a molecular level of detail that is essential to providing new insights into pHLIP function and to facilitate design of variants with improved membrane-active capabilities.